Associations of estimated glucose disposal rate with kidney stones in U.S. non-diabetic adults and possible mediating mechanisms: NHANES 2009–2020 - Haowen Liang; Ying Wei (PLoS ONE, 2025)
Background Kidney stone formation has been linked to insulin resistance (IR). However, the association between the estimated glucose disposal rate (eGDR) – a novel surrogate marker for IR – and kidney stone occurrence in non-diabetic adults remains unclear. Methods We analyzed data from adult participants in the National Health and Nutrition Examination Survey (NHANES) collected between 2009 and 2020 who self-reported a history of kidney stones. To assess the relationship between eGDR and kidney stones, we applied a range of statistical methods, including weighted proportions, multivariable logistic regression, restricted cubic splines (RCS), receiver operating characteristic (ROC) curve analysis, subgroup analysis, and mediation analysis. Results The final analysis included 8,051 participants, of whom 8.71% reported a history of kidney stones. Multivariable logistic regression revealed that, compared to the lowest eGDR quartile, the fully adjusted odds ratios (95% confidence intervals) for kidney stone in the second, third, and fourth quartiles were 0.87 (0.61–1.26), 0.54 (0.34–0.85), and 0.46 (0.28–0.77), respectively. The RCS plot indicated a significant non-linear inverse association between eGDR and kidney stone risk. ROC curve analysis showed that the association between eGDR and the risk of kidney stones was more pronounced compared to the other five IR indicators, as evidenced by a higher area under the curve. Mediation analysis identified albumin (ALB) and red cell distribution width (RDW) as partial mediators in the association between IR and kidney stones. Conclusion Our research results indicate that lower levels of eGDR are associated with an increased risk of developing kidney stones in non-diabetic adults. Furthermore, ALB and RDW may partially mediate the relationship between IR and kidney stones.